Nurses experience on home care competence development: Grounded Theory - Fernanda Catafesta; Maria Ribeiro Lacerda; Ingrid Meireles Gomes; Ana Bárbara Hoffmann Correa (Online Brazilian Journal of Nursing, 2009)
Home care means an efficient option to prevent, promote and recover population health in an integral way. Professionals in this context are required competent practice, action ultimately grounded by techno-scientific professional knowledge, not strictly bound to it, though. Considering the theme relevance, this qualitative study was elaborated objectifying to identify how nursing competences for home care are developed, and thus build a theoretical model displaying these competences from nurses’ lived experience. Consequently, Grounded Theory methodology, whose basic assumption is to build a theoretical model grounded by studied reality-based data. Seven self-employed home care nurses participated in the study for data collection from public and private institutions respectively. Dat a collection was carried out by means of a semi-structured interview, data analyzed and similiarity-grouped in categories, keeping connection between each other. Six categories resulted from the analysis which helped unveil the phenomenon: Developing competences for home care practice – nurses’ experience. As for considerations, this study contributes to practice once nurses can assess their professional activity and think over the aspects to be completed and refined. In addition, such implications are not restricted to home care as in any caring practice, nurses must be competent and develop competences.